Sonia P. Anderson, An english consul in Turkey. Paul Rycaut at Smyrna, 1667-1678 - Κιτρομηλίδης, Πασχάλης Μ. (Δελτίο Κέντρου Μικρασιατικών Σπουδών, 1993)
[ Δε διατίθεται περίληψη / no abstract available]